Baseline studies on spat collection, offshore culture and pearl culture of winged pearl oyster pteria sterna (gould 1851) on the coast of Piura, Perú - Rojas Hurtado, Daniel (2021)
Baseline studies on spat collection, offshore culture and pearl culture of winged pearl oyster pteria sterna (gould 1851) on the coast of Piura, Perú Between 2017 and 2018, extensive cultivation and pearl culture experiments were carried out with the Panamic winged pearl oyster Pteria sterna (Bivalvia: Pteriidae) on the coast of Los Órganos and Cabo Blanco (Piura, Peru). Three objectives were evaluated in sequential phases: collectors’ spat collection efficiency (sites and depth), offshore cultivation in two types of artifacts (survival and growth), and trials on pearl culture by implantation (Mabe) and surgical (free pearl) techniques. The results demonstrated the feasibility of promoting community development of pearl farms in the region.